Analysis of metabolism-related indicators and MTHFR gene polymorphism in patients with H-type hypertension - Tang, Zhi; Xiao, Ling; Wang, Ji-Qun; Zhang, Tao (Minerva medica, 2017)
This study aims to analyze the polymorphism of the methylene tetrahydrofolate reductase (MTHFR) gene in patients with hypertension, and explore the correlation between H-type hypertension and metabolic biochemical indicators such as homocysteine (Hcy). One hundred patients with H-type hypertension and 100 patients with common hypertension were selected as the study subjects. Plasma Hcy and blood lipids, blood glucose, and other biochemical indicators were detected in the two groups. Then, the polymorphism of the MTHFR gene was compared between these two groups. Hcy, uric acid (UA) and creatinine (Cr) levels in the H-type hypertension group were significantly higher than those of the common hypertension group (t=4.832-14.989, P<0.05). The T allele was predominant in the MTHFR 677C/T genotype frequency distribution in the H-type hypertension group, while the C allele was predominantly in the frequency distribution in the common hypertension group (P<0.05). High levels of Hcy, UA and Cr are closely related to the occurrence of H-type hypertension. Homozygous mutant TT genotype of 677C/T of the MTHFR gene may be an important genetic factor of H-type hypertension.